Are Precious Metals Hedging Assets for Clean Energy Indices? - Amândio, Helena; Dias, Rui; Galvão, Rosa; Alexandre, Paulo; Gonçalves, Sidalina; Leote, Francisco (Journal of Ecohumanism, 2025)
This study aims to analyse whether precious metals can be hedged assets concerning green energy indices from 8 January 2019 to 6 December 2024. About precious metals, the futures market was analysed: copper (HGH5) and silver (SIH5), the gold spot market (XAU) was also included to provide robustness, and the green indices are S&P Global Clean Energy (SPGTCLEN), NASDAQ Clean Edge Green Energy (CELS), and the iShares Global Clean Energy ETF (ICLN). The sample was divided into four sub-periods: 8 January 2019 to 31 December 2019, referred to as Pre-Covid-19; the second sub-period, referred to as the first Covid-19 Wave, comprises the period from 2 January 2020 to 31 December 2020; the second Covid-19 Wave includes the years from 2 January 2021 to 23 February 2022; Finally, the last sub-period, called Conflict, covers the years from 24 February 2022 to 6 December 2024. The green indices (CELS, ICLN, SPGTCLEN) showed extremely high correlations with each other in all periods, reducing the effectiveness of diversification in the sector. Gold remained a consistent, safe haven asset, with negative or very low correlations with the green indices, especially during global crises. Silver evolved from moderate to negative correlations with the green indices, reinforcing its usefulness as a hedging asset. Copper, initially positively correlated with green indices, has exhibited negative correlations recently, making it a strategic asset in portfolios with green energy assets. It was also found that only copper (HGH5) was contagious during the first wave of COVID-19, which validates the evidence found earlier through unconditional correlations. In conclusion, these results highlight that gold and silver effectively protect against market shocks, while copper can be used as a diversifying asset in green energy portfolios, thus requiring differentiated strategies to maximise diversification benefits.